The Senses of Sight in Lancelot Andrewes’s Sermons - Norris, Paul (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Lancelot Andrewes constructed visually intense scenes and symbolic images to capture his auditors’ interest, but he never let them forget that his visual enargia was rooted in the words of scripture and had no reality outside that given by God’s Word. His strategy was, therefore, not only to make Christ’s presence concrete and accessible to his listeners, but also to hint at how God will always be out of reach, a truth that cannot be seen. In exploring this rhetorical strategy, I focus especially on Andrewes’s 1604 Good Friday sermon, 1620 Easter sermon, and 1620 consecration rite. The two sermons were delivered at opposite ends of Andrewes’s career in James’s court, but both are notable for their intense scrutiny of what it means to see Christ in the eyes of the mind, body, and soul.